The Application of Green Accounting in Industrial Wastewater Management - Muh Fuad Randy; Fitri Indah Sari M; Husain Husain; Hasan Hasan (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to examine the application of green accounting in waste management at PT. ABCDE, focusing on five stages of environmental cost allocation: identification, recognition, measurement, presentation, and disclosure. Research Method: This research used a descriptive qualitative approach. Data were collected through interviews, observation, and documentation at PT. ABCDE is a company that manages liquid waste from production processes. Data were analyzed using the Miles and Huberman model, consisting of data reduction, data presentation, and conclusion drawing. Results and Discussion: The findings show that PT. ABCDE has applied green accounting in the stages of recognition, measurement, and disclosure. Environmental costs are recognized on an accrual basis, measured using historical cost, and disclosed in the notes to the financial statements. However, the identification and presentation stages are not fully aligned with applicable accounting standards because environmental costs are still combined with general administrative expenses. This indicates that the company’s environmental cost reporting requires further improvement. Implications: The study suggests that PT. ABCDE should separate environmental costs from general expenses and present them more transparently in financial reports. Originality: This study provides specific insight into the implementation of green accounting based on five environmental cost allocation stages in liquid waste management.